REVIEW KONSTANTA-KONSTANTA KINETIKA PERTUMBUHAN BAKTERI-BAKTERI ANAEROBIK PADA PEMBUATAN BIOGAS DARI KOTORAN SAPI (Review of Growth Kinetic Constants of Anaerobic Bacterias Involved on Biogas Production from Cow Manure) - Wresta, Arini (Baristand Industri Banda Aceh, 2014)
The important parameters needed for process and digester design in biogasproduction are kinetic constants. This research will study these constants for biogasproduction from cow manure. The study is based on anaerobic bacterias cell growthkinetic with simplifying the organic degradation to biogas in one main step that is done bymathanogenic bacterias, and the value of Î¼g is represented by Monod Equation. From thisresearch it is obtained the value of kinetic constant for cow manure biogas productioni.e. , , CH VS Y 4 / , CO VS Y 2 / , VS X Y / , CH X Y 4 / and CO X Y 2 / respectively of 0,0433 day-1 to0,1386 day-1, 21,23 mg/L, 478,42 L CH4/kg VS, 438,02 L CO2/kg VS, 30,9278 g VS/g sel,14,7965 L CH4/g cell, dan 13,5470 L CO2/g cell.